Рецензія на збірник наукових праць - Iuliia Pavlova (Lesya Ukrainka Volyn National University, 2021)
Dimitrova, R., & Wiium, N. (2021) (Eds.). Handbook of positive youth development. Advancing research, policy and practice in global contexts. Springer